Filled Prescriptions for Opioids After Vaginal Delivery. Issue 3 (March 2017) - Jarlenski, Marian; Bodnar, Lisa M.; Kim, Joo Yeon; Donohue, Julie; Krans, Elizabeth E.; Bogen, Debra L.
Abstract : OBJECTIVE: To estimate the prevalence of filled opioid prescriptions after vaginal delivery. METHODS: We conducted a retrospective cohort study of 164, 720 Medicaid-enrolled women in Pennsylvania who delivered a liveborn neonate vaginally from 2008 to 2013, excluding women who used opioids during pregnancy or who had an opioid use disorder. We assessed overall filled prescriptions as well as filled prescriptions in the presence or absence of the following pain-inducing conditions: bilateral tubal ligation, perineal laceration, or episiotomy. Outcomes included a binary measure of whether a woman had any opioid prescription fill 5 days or less after delivery and, among those women, a second opioid prescription fill 6–60 days after delivery. Among women with no coded pain-inducing conditions at delivery, we used multivariable logistic regression with standard errors clustered to account for within-hospital correlation to assess the association between patient characteristics and odds of a filled opioid prescription. RESULTS: Twelve percent of women (n=18, 131) filled an outpatient opioid prescription 5 days or less after vaginal delivery; among those women, 14% (n=2, 592, or 1.6% of the total) filled a second opioid prescription 6–60 days after delivery. Of the former, 5, 110 (28.2%) had one or more pain-inducing conditions. Predictors of filled opioid prescriptions with no observed pain-inducing condition at delivery included tobacco use (adjusted odds ratio [OR] 1.3, 95% confidence interval [CI] 1.2–1.4) and a mental health condition (adjusted OR 1.3, 95% CI 1.2–1.4). Having a diagnosis of substance use disorder other than opioid use disorder was not associated with filling an opioid prescription 5 days or less after delivery, but was associated with having a second opioid prescription 6–60 days after delivery (adjusted OR 1.4, 95% CI 1.2–1.6). CONCLUSION: More than 1 in 10 Medicaid-enrolled women fill an outpatient opioid prescription after vaginal delivery. National opioid-prescribing recommendations for common obstetrics procedures such as vaginal delivery are warranted. Abstract : More than 1 in 10 Medicaid-enrolled women fill an outpatient opioid prescription after vaginal delivery.